Think: the life of the mind and the love of God - Piper, John (Crossway, 2010)
My pilgrimage -- Deep help from a dead friend -- What do I mean by thinking? -- The place of thinking in coming to faith : mental adultery is no escape -- The place of thinking in coming to faith : rational gospel, spiritual light -- Treasuring God with all your mind -- Jesus meets the relativists -- Exposing relativism -- Unhelpful anti-intellectual impulses in our history -- You have hidden these things from the wise and understanding -- In the wisdom of God the world did not know God through wisdom -- The knowledge that loves -- All scholarship for the love of God and man